LINGUISTIC POETICS: THEORETICAL FOUNDATIONS AND APPLICATION IN LITERARY TEXTS - G’ayratova Gulzoda San’at qizi (TADQIQOTLAR, 2025)
Annotation:  This  article  discusses  the  theoretical  foundations  of  linguistic poetics, its connection with linguistics and literary studies, as well as the methods of linguistic  analysis  of  poetic  devices  in  literary  texts.  Special  attention  is  given  to metaphor, epithets, phraseological units, and syntactic devices, along with their poetic functions.